Support for adult biological fathers during termination of their partners' pregnancies - Marie Myburgh; Antoinette Gmeiner; Sandra van Wyk (AOSIS, 2001)
Nobody denies the fact that termination of pregnancy has an effect on women, but very few people realise that termination of pregnancy also has a major impact on men. Opsomming Niemand ontken dat die beëindiging van swangerskap 'n uitwerking op die vrou het nie, maar baie min mense besef dat die beëindiging van swangerskap ook 'n beduidende invloed op mans het. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.